#TITLE_ALTERNATIVE# - Putri Samsu Wibowo , Maharani
Capital market is growing rapidly not only in Indonesia but all countries over theworld, and being chosen by investors as one of an attractive investment tools. Manytheories exist among the academicians and investors based from the empirical studyand also past experiences from stock market. The theory that prominent now isFama and French (1992). They change the paradigm of many academicians thinkingthat already believe on the Capital Asset Pricing Model that founded by Sharpe,Lintner and Black (SLB) about the positive correlation between market beta andstock expected returns. FF can discovered a model that consider the characteristicsof stock that did not covered in SLB model, which is size and book-to marketequity. This paper examines the relationship between expected stock return, overall marketfactors and firm size only, not include the book-to-market equity ratio, in Indonesiafrom December 2003 to May 2007. The regression model that used in this paperfollows the FF model. This paper also investigated the January effect, by separatingthe January and non-January months in the empirical analysis to prove that FFmodel is not anomalies. The motivation of this paper comes from the fact that lack of research and very littlescientific evidence that available about Indonesia stocks market. This paper aims toprovide both investors and researchers, especially in Indonesia, with a greaterbreadth and depth understanding in the area of asset pricing techniques. At aminimum, this research already did a reasonable job in explaining the variation instocks returns challenging the tradition of the SLB model that believe by mostinvestors and researchers.